2014
DOI: 10.1920/re.ifs.2014.0098
|View full text |Cite
|
Sign up to set email alerts
|

Retirement in the 21st century

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…In the same vein, Asebedo and Payne (2019) indicated that a high level of financial self-efficacy supports financial behaviors necessary for retirement financial planning. For instance, people with high FSE are founded to be more professional in evaluating risk investment for their retirement plans (Dulebohn, 2002), to get ready for early retirement (Wo¨hrmann et al, 2013), and more likely to put their knowledge into action, which indicates a positive impact between FSE and investment decision making (Husnain et al, 2019;Lunceford, 2017). These studies highlight the positive relationship between FSE with FPR behaviors.…”
Section: Capacity To Plan and Save For Retirement-financial Self-effi...mentioning
confidence: 99%
“…In the same vein, Asebedo and Payne (2019) indicated that a high level of financial self-efficacy supports financial behaviors necessary for retirement financial planning. For instance, people with high FSE are founded to be more professional in evaluating risk investment for their retirement plans (Dulebohn, 2002), to get ready for early retirement (Wo¨hrmann et al, 2013), and more likely to put their knowledge into action, which indicates a positive impact between FSE and investment decision making (Husnain et al, 2019;Lunceford, 2017). These studies highlight the positive relationship between FSE with FPR behaviors.…”
Section: Capacity To Plan and Save For Retirement-financial Self-effi...mentioning
confidence: 99%